Duration of dual antiplatelet therapy and long-term outcomes following drug-eluting balloon or drug-eluting stents for treatment of in-stent restenosis (DAPT-Dragon Registry). (14th October 2021) - Januszek, R; Bil, J; Figatowski, T; Tomasiewicz, B; Desperak, P; Niezgoda, P; Reczuch, K; Kubica, J; Gil, R J; Bartus, S; Gasior, M; Witkowski, A; et al.
Abstract: Objectives: The aim of the DAPT-DRAGON registry was to asses long-term outcomes and the length of dual antiplatelet therapy (DAPT) in patients treated with percutaneous coronary intervention (PCI) due to drug-eluting stent in stent restenosis (DES-ISR) with drug-eluting balloons (DEB) or thin-DES. Background: Data regarding the duration of DAPT in patients with DES-ISR treated with PCI is still undergoing research and observation, and the adequate duration of DAPT in this group of patients is not unambiguously sanctioned. Methods: Overall, 1, 367 consecutive patients with DES-ISR who underwent PCI with DEB or DES, were entered into the multi-center DAPT-DRAGON Registry (Fig. 1). The mean age was 66.7±9 years (70.5% males). The median follow-up was 3.3 years. There were 34.1% patients with chronic coronary syndrome, 35.2% with unstable angina, 2.9% with ST segment elevation myocardial infarction and 27.7% with non-ST segment elevation myocardial infarction (MI). We assessed selected study endpoints according to the duration of DAPT (≤3 vs. >3 months and ≤6 vs. >6 months), before and after propensity score matching (PSM): stroke, target lesion revascularization (TLR), target vessel revascularization (TVR), MI, death and device-oriented composite endpoints (DOCE). Results: Among predictors of increased DOCE rate before PSM, we demonstrated: PCI with DEB vs. DES (p<0.001), recurrent ISR (p=0.002), treatment with glycoprotein IIb/IIIa inhibitor during PCI (p<0.001), lower left ventricle ejection fraction (p=0.004) and extent of stenosis (p<0.001). Pairwise contrast analysis considering type of PCI (thin-DES vs. DEB) and duration of DAPT (≤6 vs. >6 months) before PSM revealed superiority of thin-DES+DAPT >6 months vs. DEB+DAPT >6 months for DOCE (p<0.001), TVR (p=0.02) and TLR (p=0.01). After PSM analysis, the length of DAPT (≤3 vs. >3 months) had no significant influence on assessed long-term outcomes, while the percentage of stroke free survival was significantly lower in the group of patients with DAPT ≤6 months vs. >6 months (p=0.01; Fig. 2). Conclusions: Long-term treatment with DAPT (>6 months) in patients with DES-ISR with DES implantation is related to better long-term outcomes in terms of lower rate of DOCE, TVR and TLR compared to PCI with DEB. DAPT >6 months is related to a greater rate of strokes, independently of the type of treatment (thin-DES and DEB) compared to DAPT ≤6 months. FUNDunding Acknowledgement: Type of funding sources: None.